Analysis of Factors and Impact of Achievement on Students Career and Self Development - Mutaufiq, Ali; Trimulyana, Robi Amdes; Sunarsi, Denok (Sharia Business Management Department of STEBIS Bina Mandiri, 2025)
This study aims to analyze the factors influencing academic achievement and its impact on students' career and self-development. The primary focus is to understand how internal factors such as motivation, self-confidence, and study discipline, as well as external factors such as family support, school environment, and educational policies, contribute to students' success. This research employs a quantitative approach using a survey method involving students from various educational levels. Data were collected through questionnaires designed to measure variables related to academic achievement and its impact on career development and self-improvement. Data analysis was conducted using descriptive statistics and regression analysis to identify relationships between these variables. The findings indicate that internal factors, particularly intrinsic motivation and study discipline, have a significant impact on students' academic achievement. Additionally, family support and a conducive school environment also contribute positively. Furthermore, high academic achievement is strongly associated with increased self-confidence in career planning and enhanced self-development skills such as leadership and communication.